Socio-demographic Profiles of Cervical Cancer Patients at Cipto Mangunkusumo Hospital - 2009-2019 and Its Association with Cancer Stages at Diagnosis - Fitriyadi Kusuma; Kemal Akbar Suryoadji; Michael Adrian; Tofan Widya Utami; Hariyono Winarto; Tricia Dewi Anggraeni; Kartiwa Hadi Nuryanto; Muhammad Haekal (PT. Kalbe Farma Tbk., 2022)
Objective: To determine the socio-demographic profile of cervical cancer patients at Cipto Mangunkusumo Hospital in 2009-2019 based on educational level, parity, age, residence, and employment status and their relationship to cervical cancer stage at diagnosis. Methods: Comparative analytical study was conducted retrospectively based on medical records in Cipto Mangunkusumo Hospital. The selection was based on data completeness: cervical cancer stages, sociodemographic profiles consisting of education level, parity, age, Java or non-Java Island resident, and occupation. Multivariate analysis calculated the association between socio-demographic factors and cervical cancer stages. Data were analyzed using SPSS v.22.0 and Microsoft Excel. Results: This study included 4,584 patients with complete data. Only 19.3% patients were in the early stage, 63.3% had less than three parities, 82.8% of patients had formal primary school education or less, 80.9% patients were aged 18-65 years, 88.3% patients resided in Java Island, and 80.5% didn’t have the occupation. There was a significant association (p <0.05) between cervical cancer stage and educational level (aOR= 0.86; 95% CI= 0.78-0.94) and age (aOR= 1.46; 95% CI= 1.18-1.40). There is no significant association (p >0.05) between cervical cancer stage and parity, residence, and employment status. Conclusion: Low education and old age (> 65-year-old) were associated with the advanced stage of cervical cancer at diagnosis. Tujuan: Mengetahui profil sosiodemografi pasien kanker serviks di Rumah Sakit Cipto Mangunkusumo tahun 2009-2019 berdasarkan tingkat pendidikan, jumlah paritas, usia, status kependudukan, pekerjaan, serta hubungannya terhadap stadium kanker serviks saat diagnosis. Metode: Penelitian analitik komparatif retrospektif berdasarkan data rekam medis Rumah Sakit Cipto Mangunkusumo. Pemilihan sesuai kelengkapan data: stadium kanker serviks, profil status sosiodemografi yang terdiri atas tingkat pendidikan, paritas, usia, penduduk pulau Jawa atau non-Jawa, dan status pekerjaan. Hubungan antar variabel dianalisis multivariat untukmencari hubungan berbagai faktor sosiodemografi terhadap stadium kanker serviks. Analisis data menggunakan program SPSS versi 22.0 dan Microsoft Excel.Hasil: Terdapat 4.584 pasien kanker serviks yang memenuhi kriteria inklusi. Sebanyak 19,3% pasien dengan stadium awal. Selanjutnya 82,8% pasien memiliki pendidikan formal sekolah dasar atau kurang, 63,3% pasien memiliki jumlah paritas kurang dari tiga, 80,9% pasien berusia antara 18-65 tahun, 88,3% pasien berdomisili di pulau Jawa, dan 80,5% tidak bekerja. Didapatkan asosiasi bermakna (p<0,05) antara stadium kanker serviks dan tingkat pendidikan (aOR = 0,86; 95% CI= 0,78-0,94) dan usia (aOR= 1,46; 95% CI= 1,18-1,40). Tidak ditemukan asosiasi bermakna (p>0,05) antara stadium kanker serviks dengan paritas, domisilikependudukan, dan status pekerjaan. Simpulan: Tingkat pendidikan rendah dan usia lanjut (>65 tahun) berasosiasi dengan stadium lanjut kanker serviks saat diagnosis.